Laporan Kasus Berbasis Bukti: Dapatkah Indeks Mentzer Membimbing Diagnosis Anemia Mikrositik di Daerah Rural Indonesia? - Vita, Angelica Diana; Bernardinus Realino Nara, Mario (Majalah Kedokteran Indonesia, 2025)
Introduction: Indonesia, part of the “Thalassemia Belt,” carries a significant burden of hemoglobinopathies, with β-thalassemia trait (BTT) affecting up to 10% of the population. In rural settings with limited access to advanced diagnostics, distinguishing between BTT and iron deficiency anemia (IDA) using clinical and hematologic indices such as the Mentzer Index may aid early management.Method: A structured literature search was conducted in MEDLINE and EBSCO to identify diagnostic or cross-sectional studies comparing red blood cell indices, particularly the Mentzer Index, in differentiating IDA from BTT. Studies were selected based on inclusion and exclusion criteria, and full texts were critically appraised by three reviewers using criteria of validity, importance, and applicability.Results: Six studies with Level 4 evidence were included. The Mentzer Index was evaluated in all studies, with sensitivity ranging from 66% to 100% and specificity from 47.1% to 100%. Rashwan et al. and Jasim et al. reported perfect or near-perfect accuracy, while Indrasari et al., an Indonesian study, found more modest results (sensitivity 66%, specificity 62.5%). Variability in diagnostic performance may be influenced by population genetics, disease spectrum, and laboratory techniques.Conclusion: The Mentzer Index demonstrates promising diagnostic value, particularly in settings where advanced testing is unavailable. However, variability in its accuracy across populations suggests that clinical judgment remains essential. The Mentzer Index can be a useful preliminary tool but should not replace confirmatory tests when available.